Sustained posterior negativity (SPN) elicited by brief (20 ms) symmetrical stimuli - Contemori, Giulio; Musa, Marianna; Demirkapi, Deniz; Passaggi, Martina; Oletto, Carolina Maria; Battaglini, Luca; Bertamini, Marco (Frontiers in Psychology, 2026)
IntroductionMirror symmetry is detected rapidly, yet it remains unresolved whether its canonical neural signature—the Sustained Posterior Negativity (SPN)—requires extended viewing. We therefore asked whether symmetry-selective activity can be generated under highly constrained temporal conditions that limit both prolonged processing and premotor preparation.MethodsWe presented centrally displayed, irregular octagons (symmetric or asymmetric) for 20 ms while preventing premotor preparation via a delayed, trial-wise randomized response mapping. EEG was recorded with a 64-channel montage and preprocessed using a fully scripted, automated pipeline; ERPs were computed from correct trials only. Symmetry-related activity was first assessed with a mass-univariate, cluster-based permutation analysis, and then quantified in a confirmatory analysis within a canonical posterior region of interest. A fixed-cohort trial-subsampling analysis was used to examine how per-condition epoch count affects SPN estimation.ResultsThe cluster-based permutation analysis revealed a mid-latency posterior negativity with the occipito-parietal topography characteristic of the SPN, and the canonical posterior region-of-interest analysis converged on the same effect. Behaviorally, participants discriminated symmetry reliably with a modest liberal bias. Fixed-cohort trial subsampling showed that increasing per-condition epochs enhanced statistical detectability without altering amplitude, indicating precision gains rather than changes in the underlying response. No reliable condition differences were observed in earlier sensory components, and there was no compelling hemispheric lateralization.DiscussionThese results demonstrate that brief visual evidence is sufficient to initiate symmetry-selective activity that unfolds over the established SPN time course in the absence of sustained viewing or response preparation. This pattern supports a hybrid account in which a rapid feedforward sweep flags global regularity while recurrent interactions sustain and consolidate the representation, thereby tightening temporal constraints on the neural mechanisms that extract structural order from transient input.